Knowledge Gaps and Self-Care Challenges Among Elderly Hypertensive Patients: Barriers, Influencing Factors, and the Need for Adaptive Interventions - Suharyanti, Bernadhea Agnes; Pujiastuti, Theresia Tatik; Nekada, Cornelia Dede Yoshima (Universitas Tribhuwana Tunggadewi, 2025)
Hypertension, a non-communicable disease often called the